Kolaborasi Internasional dalam Pengabdian kepada Masyarakat: Program Pertukaran Dosen untuk Pemberdayaan Komunitas antara Universiti Malaysia Sabah dan Universitas Borneo Tarakan - Apriadi, Dodi; Shalahuddin, Shalahuddin; Yusof, Nor Afifah; Jimainal, Mohd Noor Hidayat (Universitas Borneo Tarakan, 2024)
The Lecturer Exchange Program held on November 21, 2024, between the Faculty of Business, Economics, and Accounting at Universiti Malaysia Sabah (UMS) and the Faculty of Economics at Universitas Borneo Tarakan (UBT) aims to strengthen academic cooperation and improve the quality of learning in the fields of management and economics. This event involved guest lecturers from UMS, Dr. Nor Afifah Yusof and Dr. Mohd Noor Hidayat Jimainal, who delivered lectures on the topic Virtual Research Collaboration: How Much Does That Work? to UBT's Faculty of Economics students. Additionally, course instructors at UBT, Dr. Shalahuddin and Dodi Apriadi, were also actively involved in this event. The program is expected to provide global insights and enrich the learning process for UBT students, as well as strengthen the relationship between the two universities. This article outlines the objectives, implementation, benefits, and impact of the activity as a form of community service in higher education.